Study on the Mechanism of Coal Fracturing by Liquid Nitrogen - Wang, Haifeng (International Journal of Natural Resources and Environmental Studies, 2024)
As a fracturing medium with excellent properties, liquid nitrogen has multiple fracturing effects on coal, and its potential application in coalbed methane mining has become a hot spot in current research. In this paper, the key scientific problems of fracturing and penetration enhancement by liquid nitrogen in low-permeability coals are discussed in depth, and the pore fracturing process and its fracturing mechanism of low-temperature fracturing coal are analyzed. It is found that the ultra-low-temperature fluid fracturing process has the effect of high-energy fluid fracturing to break the rock, and also has the coupled fracturing effect of low-temperature fracturing and phase-change fracturing to increase the energy-driven replacement. It aims to provide theoretical basis and technical support for the efficient and environmentally friendly exploitation of low-permeability oil and gas fields.